Dasar Integrasi Ilmu dalam Alquran - Firdaus, Firdaus (UIR Press, 2019)
Abstrak: The danger of secularization has spread to our education. Dichotomy of science we feel is very thick. In reality, there is a gap between the science of religion and world science. Islam is not familiar with science dichotomy. Because according to Islam, science has a purpose to worship Allah. To eliminate the paradigm, Islam provides a solution that is scientific integration. The integration of this science has purpose to return the essence of science that is to worship Allah and instill morals and values in people who study science.